ALTERNATIVE MATRICES FROM THE ORAL CAVITY AS A SOURCE FOR DRUG DETECTION - Ambarioni, Agnes; Prayudha, Anggy (Jurnal Biosains Pascasarjana, 2025)
Forensic toxicology plays a crucial role in law enforcement by detecting xenobiotic substances in the human body, aiding in legal decisions. Traditional matrices like blood and urine have significant drawbacks, such as invasiveness, susceptibility to adulteration, and limited detection windows. This paper explores alternative matrices from the oral cavity, including oral fluid, teeth, dental plaque, and dental calculus, for drug detection. Oral fluid offers non-invasive collection and reliable pharmacokinetic data, while teeth provide long-term drug detection in postmortem cases. Dental plaque and dental calculus can trap substances over time, offering insights into past drug use with less invasive sampling. These matrices reflect the overall condition of the body and provide valuable forensic information. Continued research and technological advancements are necessary to optimize their application in various forensic scenarios.